It’s Not Easy Being Green: The Development of ‘Food Safety’ Practices in New Zealand’s Apple Industry - McKenna, Megan; Campbell, Hugh (The International Journal of Sociology of Agriculture and Food, 2021)
Through a discussion of ’industry greening’ this paper reviews different attempts by New Zealand’s apple industry to address the issue of food safety and protect its global market niche in the fresh fruit and vegetables complex. Conceptually, we argue that agri-food research has too long neglected the importance of re-theorising ’scale’ in explaining contemporary changes in food production and consumption. Recognising scale as something that is produced and non-hierarchical, this paper suggests that the manner in which ’green’ food discourses are contested shapes regulatory industry structures, production practices and the ways we engage nature with bio-politics. Such processes are explored through an examination of the development of both Integrated Fruit Production (IFP) systems and organic production within New Zealand’s apple industry. The results display a complex interweaving of the politics of industry ‘greening’ with the politics of deregulation within the apple industry. The eventual structuring of IFP and organic practices clearly demonstrate the importance of scale as a dynamic rather than neutral aspect of the restructuring of food production sectors.